Multicenter evaluation of ceftolozane/tazobactam for serious infections caused by carbapenem-resistant pseudomonas aeruginosa (2020)
A multicenter, retrospective study of patients infected with carbapenem-resistant Pseudomonas aeruginosa who were treated with ceftolozane/tazobactam was performed. Among 35 patients, pneumonia was the most common indication and treatment was successful in 26 (74%). Treatment failure was observed in all cases where isolates demonstrated ceftolozane-tazobactam minimum inhibitory concentrations ≥8 μg/mL.